Coconut Culture and Jekyll-and-Hyde: A Study of Self Dynamics among Second Generation British-Asians - Sharma, Deepika; Wagoner, Brady (Studia Psychologica: Theoria et praxis, 2008)
The self is composed of I-positions that become intelligible only within a given cultural framework, which can be thought of as the ground upon which figures appear. Thus, we arrive at a two level self-system, where I-positions (level 1) are organized by cultural frameworks (level 2) that subsume multiple positions within a generalized position (like Mead’s “generalized other”). These levels correspond to what has been called polyphony and cognitive polyphasia, respectively. The former refers to particular voices through which we think/speak whereas the latter is about entire patterns of group thinking. To illustrate the relationship between polyphony and polyphasia we interviewed second generation British-Asians, who simultaneously belong to two very different cultural groups. The subject, who we focus on in our analysis, uses multiple voices to answer the question if she would tell her mother about her smoking, but she also navigates between two distinct frameworks in the process, the Asian and the British. Self-dialogue can thus be understood not only at the level of particular I-positions, but also at a more general level of confrontation between these two frameworks.